A review on cable yarding operation performance and its assessment. Issue 2 (4th May 2023) - Böhm, Stephan; Kanzian, Christian
ABSTRACT: Cable yarding is a well-established practice for wood extraction in mountainous regions in most parts of the world where fully mechanized harvesting systems like harvester-forwarder combinations cannot operate due to steep terrain. Work- and time-studies are most relevant to create productivity models for cost estimation, simulation, system development or simply to compare different harvesting systems. The present work investigates 70 work studies on cable yarding operations, regarding assessment methods to establish a knowledge base on cable yarding performance models. A comprehensive literature research was performed to identify relevant studies. Information about the investigated extraction campaigns regarding site specifics, stock specifics, the utilized equipment alongside the work-study-methods, as well as the statistical approaches for model creation were collected. The data gained and the associated models were systematically analyzed to compare different yarding systems concerning their performance. A set of 98 models was selected for this purpose. Productivity of the investigated systems ranges from 1.5 m 3 /PSH to 69.3 m 3 /PSH with a mean value of 9.8 m 3 /PSH where PSH represents the productive system hour. A meta-analysis was performed with the data that is presented in the literature found to test several hypotheses concerning the influence of different parameters on the performance of yarding systems. Various relationships are so strong that regression analysis with the meta-dataset, that is mostly containing mean values presented, results in significant correlations. The diversity in problem formulation and the corresponding diversity in methodical approaches account for limitations in comparability of performance. The consultation of guiding literature on forest work studies can promote comparability between studies.